Efektifitas Penerapan Pola Asuh Orang Tua, Ekstrakurikuler, Dan Media Sosial Terhadap Kepribadian Siswa Di SMK Muhammadiyah - Retyana Wahrini (Universitas Islam Raden Rahmat Malang, 2024)
The aim of this research was to investigate correlation of : (1) Parenting to student personality of SMK Muhammadiyah 2 Moyudan Yogyakarta, (2) Extracurricular to student personality of SMK Muhammadiyah 2 Moyudan Yogyakarta, (3) Social Networking to student personality of of SMK Muhammadiyah 2 Moyudan Yogyakarta, (4) Parenting, Extracurricular, and Social Networking jointly to student personality of of SMK Muhammadiyah 2 Moyudan Yogyakarta. Type of research was ex post facto by using a quantitative approach. The independent variables of this research are Parenting, Extracurricular, and Social Networking. The dependent variable of this research is student personality. The data were collected through a questionnaire and documentation. The population consists of 55 students from class X student of electrical expertise in of SMK Muhammadiyah 2 Moyudan Yogyakarta, which the entire population is the subject of research. Data were analyzed with correlation product moment techniques and multiple regression techniques. The results of the research at the 5% level of significance show that were : (1) positive and significant correlation of Parenting to student personality of of SMK Muhammadiyah 2 Moyudan Yogyakarta posed at with t_obtained 5,165 > t_table 2,006. (2) positive and significant correlation of Extracurricular to student personality of of SMK Muhammadiyah 2 Moyudan Yogyakarta posed at with t_obtained 5,460 > t_table 2,006. (3) negative and no significant correlation of Social Networking to student personality of of SMK Muhammadiyah 2 Moyudan Yogyakarta posed at with t_obtained -0.638 < t_table 2,006. positive and significant correlation of Parenting, Extracurricular and Social Networking jointly to student personality of of SMK Muhammadiyah 2 Moyudan Yogyakarta posed at with F_obtained 15,354 > F_table 2,79